Mendorong Kepuasan Kerja di Organisasi Nirlaba Menurut McClelland's Human Motivation Theory (Survei Pada Pengurus Organisasi Kemahasiswaan Universitas Kristen Maranatha Bandung) - Ginting Munthe, Rusli; Gunawan, Ryan (Lentera Ilmu Nusantara, 2024)
During the transition of the pandemic to endemic covid-19, there was a decrease in the number of students who were called to become administrators of organizations, one of which was UK Maranatha. UK Maranatha is one of the private universities in Bandung City that has more than 30 student organizations, of course, the decline is related to the job satisfaction of the organization's management, especially the organizations in UK Maranatha are non-profit organizations. In fact, the percentage of active students who are called to be involved in student organization administrators is only 7.47% of the total active students of UK Maranatha class of 2020-2022 and of course this is something questionable. Based on previous research, it is known that job satisfaction is influenced most by motivation. Thus, this study assumes that effective motivation is expected to increase the level of job satisfaction of student organization administrators. This study is classified as quantitative research, primary data collection was carried out by distributing questionnaires to the administrators of the UK Maranatha student organization and as many as 326 questionnaires and only 320 questionnaires were considered worthy of further processing and the results showed that motivation affected job satisfaction by 78.2%.